Perlukah Keselamatan Pasien Menjadi Indikator Kinerja RS BLU? - Basabih, Masyitoh (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
The government which is the Ministry of Health through its regulations mandates the importance of patient safety. This can be seen from the mention of patient safety in the four articles in Undang-Undang Number 44 Year 2009 about Hospital and specifically in the Minister of Health Regulation. The importance of patient safety issues in hos pitals is not directly proportional to the performance indicators of the BLU Hospital written inPeraturan Direktur Jenderal Pembendaharaan Number 34 Year 2014 about the Guidelines for Performance Appraisal of Public Ser vice Bodies for Health Services. In this regulation, it can be seen that the performance assessment of BLU Hospital consists of financial aspect and service aspect. Patient safety can be seen in service aspect more specially can be seen in group of clinical quality indicator which have maximum score 12 from 100. Clinic quality is measured with five indicator which four of them is death rate. If it refers to the magnitude of the emphasis on patient safety and the definition of patient safety, then the question is whether the indicator of mortality adequately represents the im portance of patient safety in the hospital? This article aimed to provide an overview of the role of patient safety in the performance indicators of hospital performance BLU. This study was conducted by using the literature review method. The results of this study indicate that the patient's safety efforts have not fully become the benchmark of BLU Hospital performance.